Clarifying Muddied Waters, Part 2: What the Sudduth-Tucker Exchange Concerning James Leininger Suggests for Reincarnation Research - Matlock, James G. (Journal of Scientific Exploration, 2023)
Part 1 of this paper presented a secure timeline for the James Leininger reincarnation case, showing Michael Sudduth’s criticisms of it to be unfounded. Part 2 begins with an analysis of the exchange in this journal between Sudduth and Jim Tucker over Tucker’s investigation, then recommends improvements that might be made in the investigation and reporting of reincarnation cases to address criticisms, overcome a will to disbelieve in the evidence, and reach scientists and scholars open to following the research findings where they lead. Proposals are grouped under three headings: Case Study Methodology, Reporting Standards, and Statistical Analysis.